Multi-Stakeholder Governance Strategies in Indonesia’s Ride-Hailing Ecosystem - Yuwono D. Sucipto; Euis Saribanon; Irwan Chairudin; Osman Arofat; Reni Dian Oktaviani (Siber Nusantara of Economic and Finance Review, 2025)
The transformation of Ride-Hailing Services (RHS) into Transport Super-Apps (TSA) in Indonesia has fundamentally altered the urban mobility landscape. This article addresses the need to delineate a multi-stakeholder governance framework that aligns innovation with environmental sustainability, accessibility, and user convenience. Adopting a Systematic Literature Review (SLR) approach of current literature through 2025-2026, the primary findings indicate that the success of sustainable mobility depends on resolving the 'Mobility Trilemma': affordability, scalability, and sustainability. The analysis emphasizes three main pillars: (1) trust-based regulation, (2) acceleration of Electric Vehicle (EV) infrastructure, and (3) multimodal integration as the foundation for future RHS policy design in Indonesia. This study formulates a multi-stakeholder governance framework focusing on the roles of users, drivers, TSA platforms, and the government (central and regional), alongside cross-level policy recommendations to promote RHS as a feeder for mass public transportation.